2019
DOI: 10.1177/0363546519887909
|View full text |Cite
|
Sign up to set email alerts
|

Articular Joint-Simulating Mechanical Load Activates Endogenous TGF-β in a Highly Cellularized Bioadhesive Hydrogel for Cartilage Repair

Abstract: Background: The treatment of osteochondral defects (OCDs) constitutes a major problem for orthopaedic surgeons. The altered mechanics and the cell types, with associated soluble factors derived from the exposed subchondral bone, are likely responsible for the mechanically and structurally inferior articular cartilage subsequently obtained as a repair tissue. There is therefore an unmet clinical need for bioresponsive biomaterials that allow cell delivery, reduce cell infiltration from the bone marrow, and supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“… 125 Interestingly, for the enzymatic gelation of HA-tyramine, it was observed that the cell-induced decrease in viscoelastic properties diminishes at lower temperature, and the extent of this effect appears to vary with the embedded cell type. 152 This suggests that uptake and neutralization of reactive species might depend on the metabolic activity of the cells. A further aspect is that certain cross-linking chemistries, such as phenol–phenol coupling, thiol–ene or aldehyde-based systems, such as hydrazine-forming inks, 153 , 154 involve functional groups which are naturally present on amino acids and thereby on the cell surface.…”
Section: Rheological Factors Affecting Printability and Shape Fidelitmentioning
confidence: 99%
“… 125 Interestingly, for the enzymatic gelation of HA-tyramine, it was observed that the cell-induced decrease in viscoelastic properties diminishes at lower temperature, and the extent of this effect appears to vary with the embedded cell type. 152 This suggests that uptake and neutralization of reactive species might depend on the metabolic activity of the cells. A further aspect is that certain cross-linking chemistries, such as phenol–phenol coupling, thiol–ene or aldehyde-based systems, such as hydrazine-forming inks, 153 , 154 involve functional groups which are naturally present on amino acids and thereby on the cell surface.…”
Section: Rheological Factors Affecting Printability and Shape Fidelitmentioning
confidence: 99%
“…For instance, the extraction of high-quality RNA from complex matrixes can be particularly challenging [12,13], especially with increasing culture duration, during which time increasing amounts of extracellular matrix are produced. This is also the case of the hyaluronic acid (HA)-based biomaterials commonly used in tissue engineering studies relevant to the musculoskeletal field [14][15][16]. The three dimensionality of a biomaterial-based culture, together with the composition of HA itself, likely influence the expression of reference gene candidates over a prolonged culture period.…”
Section: Introductionmentioning
confidence: 99%
“…As the authors of this chapter are active in the field of musculoskeletal research, examples will be illustrated using connective tissues or cells isolated from bone and joints. These fields often focus on joint-derived tissues that cause clinical problems for healing such as (i) anterior cruciate ligament (ACL) [1][2][3], (ii) cartilage scaffold engineering [4][5][6][7], (iii) intervertebral disc (IVD) regeneration [8][9][10] and (iv) bone regeneration [11][12][13][14][15]. We demonstrate a subset of fluorescent staining and methods to stain cells from bone and jointderived tissues: that is, staining mesenchymal stromal cells, chondrocytes and IVD cells in native tissue or in 3D hydrogel-like scaffolds such as fibrin [16], polyethylene glycol (PEG) [17], and also cells on solid materials such as silk [18].…”
Section: Introduction 11 the Need For 3d Culture Models In Tissue Engineeringmentioning
confidence: 99%